DEVICE FOR MONITORING OPERATION OF NUCLEAR POWER PLANT - AKIZUKI, Yasutake; FUKUI, Toshiki; SHINOHARA, Hironobu; TANAKA, Yuichi; KIUCHI, Shinji; FUJIMOTO, Hiroshi; SHIRASAWA, Hiroshi (2017)
An operation monitoring apparatus is provided with a function integration VDU (21) including a normal use system VDU (32) which operates and monitors a nuclear power plant under a normal state, and a safety protection system VDU (31) which shuts down the nuclear power plant under an abnormal state, and also a safety protection system VDU (22) which shuts down the nuclear power plant under the abnormal state, and further, a block device which inhibits an actuation of the safety protection system VDU (31) when the function integration VDU (21) is under an abnormal state, thereby capable of simplifying an operation manipulation in the nuclear power plant, and ensuring a high level of safety of an operation control.